2019
DOI: 10.22373/share.v8i2.4679
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Intention to Stock Investment Among Muslim Investors in Langsa

Abstract: This study aims to examine the effect of knowledge, income and risk perceptions on the intention in stock investment intention among Muslim investors in the city of Langsa, Aceh, as of 2017. The data used in this study are primary, data derived from questionnaires, interviews, and observations. This study utilized a sample of 100 people, using a random sampling technique. The results of the study show that knowledge, income, and risk perceptions simultaneously influence the stock investment intention in Langsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 5 publications
3
9
1
3
Order By: Relevance
“…The results of this study support previous research conducted by Manurung et al (2018), which states that financial literacy, including financial knowledge, affects investment intention or interest. However, the results of this study contradict the previous research conducted by Hamid et al (2019) and Claudia and MN (2019), which in their conclusion state that financial knowledge does not affect investment intention.…”
Section: Effect Of Financial Knowledge On Investment Intentioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of this study support previous research conducted by Manurung et al (2018), which states that financial literacy, including financial knowledge, affects investment intention or interest. However, the results of this study contradict the previous research conducted by Hamid et al (2019) and Claudia and MN (2019), which in their conclusion state that financial knowledge does not affect investment intention.…”
Section: Effect Of Financial Knowledge On Investment Intentioncontrasting
confidence: 99%
“…The Effect of Financial Knowledge on Investment Intention Lim et al (2018); Manurung et al (2018) Significantly Positive There are contradictions in research results Hamid et al (2019) No significant effect The Effect of Financial Well-Being on Investment Intention Kabir et al, (2011); Guiso & Sodini, 2013 Take effect There are contradictions in research results Sivaramakrishnan et al, (2017); Sivaramakrishnan dan Srivastava (2019) No effect Source: Data processed, 2021…”
Section: Research Gapmentioning
confidence: 98%
See 1 more Smart Citation
“…Aini et al (2019) meneliti pengaruh pengetahuan, pemahaman, modal investasi minimal, return investasi dan risiko investasi dengan menggunakan sampel mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang dan Universitas Islam Negeri Maulana Malik Ibrahim menemukan bahwa hanya variabel risiko investasi yang berpengaruh terhadap minat investasi, sedangkan keempat variabel yang lain yaitu pengaruh pengetahuan, pemahaman, modal investasi minimal, return investasi tidak terbukti mempunyai pengaruh terhadap minat investasi mahasiswa. Sementara Hamid et al (2019) yang meneliti minat investasi dalam saham pada masyarakat Muslim di Kota Langsa, Aceh, pada tahun 2017 menemukan bukti bahwa pendapatan dan persepsi risiko mempunyai pengaruh signifikan terhadap minat berinvestasi, sedangkan pengetahuan investasi tidak terbukti mempengaruhi minat investasi terhadap saham. Hal ini mengindikasikan bahwa meskipun responden mempunyai pengetahuan yang cukup, tetapi mereka kurang berminat melakukan investasi dalam saham dikarenakan adanya kekhawatiran terhadap hasil yang tidak akan mencukupi kebutuhan sehari-hari sedangkan pendapatan mereka sendiri masih tergolong rendah.…”
Section: Pendahuluanunclassified
“…Knowledge and religious activities (religious behavior) of investors encourage all informants to choose instruments following sharia. Hamid et al (2019) examined Muslim investors' intention to invest in Langsa -Aceh stocks. The results showed that earnings and perceptions of risk influenced stock investment intentions.…”
Section: Introductionmentioning
confidence: 99%